Influence of Compensation, Work Culture, and Work Environment on Employee Performance: Evidence from the Department of Transportation of Ngawi Regency - Budiarti; Mintarti Indartini; Hartirini Warnaningtyas (International Journal of Business and Quality Research, 2026)
This study empirically examines the partial and simultaneous effects of compensation, work culture, and work environment on employee performance within a local government institution characterized by a high-mobility, dual-workload operational setting. Employing a quantitative causal-associative design, data were collected from 109 active civil servants at the Department of Transportation of Ngawi Regency. The sample was determined using Slovin's formula and selected via proportionate stratified random sampling to ensure representative distribution across diverse operational divisions. Data were gathered using a Likert-scale questionnaire and analyzed using multiple linear regression via IBM SPSS Statistics. The findings indicate that compensation, work culture, and work environment exert a positive and statistically significant influence on employee performance, both partially and simultaneously. Furthermore, compensation emerges as the most dominant determinant of performance in this context. The results suggest that to maintain public service integrity and operational stamina, bureaucratic institutions must prioritize equitable financial and non-financial compensation schemes alongside a cohesive organizational culture and supportive physical infrastructure.